Global challenges for identity policies - Whitley, Edgar A.; Hosein, Ian. (Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2010)
"The goals of this book are to provide a comprehensive review of identity policies as they are being implemented in various countries around the world, to consider the key arenas where identity policies are developed and to provide intellectual coherence for making sense of these various activities"--Provided by publisher.
Includes bibliographical references (p. 247-279) and index.
Keywords: Identity theft -- Prevention; Identification